Comparison of Serial and Parallel Computation on Predicting Missing Data with EM Algorithm - Nurmawati, Erna; Pangaribuan, Robby Hasan; Santoso, Ibnu (Jurnal Matematika, Statistika dan Komputasi, 2021)
One way to deal with the presence of missing value or incomplete data is to impute the data using EM Algorithm. The need for large and fast data processing is necessary to implement parallel computing on EM algorithm serial program. In the parallel program architecture of EM Algorithm in this study, the controller is only related to the EM module whereas the EM module itself uses matrix and vector modules intensively. Parallelization is done by using OpenMP in EM modules which results in faster compute time on parallel programs than serial programs. Parallel computing with a thread of 4 (four) increases speed up, reduces compute time, and reduces efficiency when compared to parallel computing by the number of threads 2 (two).